REORIENTASI DAYA TAWAR PERAN PEREMPUAN DALAM RUANG PUBLIK PADA RANAH ORGANISASI SOSIAL ISLAM - Jailani, Imam Amrusi (Sunan Kalijaga State Islamic University & The Asia Foundation, 2012)
Observing the relationship between men and women, actually recognized the existence of two relationships that are connotative be distinguished, that, sexual relations and gender relations. Sexual relationship is the relationship between men and women based on the demands and biological categories. Whereas gender relations is a concept and a different social reality, in which the sexual division of labor between men and women is not based on an understanding of normative and biological categories, but on the quality, skills, and roles based on social conventions. Thus, the concepts and manifestations of gender relations more dynamic and has the flexibility to consider psycho-social variables were developed. Based on this understanding, it could be someone who is biologically classified as a woman, but from the point of gender may play a role as a man or vice versa. Therefore, we need to reorient the roles of women, especially their involvement in the organization of the Islamic community, which often marginalized.